2020
DOI: 10.1080/17524032.2020.1725086
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Scientific Source Credibility and Goodwill in Public Skepticism Toward GM Foods

Abstract: The complex web of political-economic relations that constitutes biotechnology coupled with a contentious history of public resistance, illustrates the power of perceptions of credibility in mediating individuals' judgements about GMOs. To more accurately measure what contributes to public skepticism of GM foods, the present research applies a multidimensional model of source credibility comprised of scientific understanding, integrity, agreement, concern, trust, and goodwill (bias). Testing the Anti-Reflexivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…It may be because consumers have different perceptions of whether tomatoes and corn are GM foods compared to soybeans and rice, which results in insignificant effects. Previous studies have also pointed out the difference in the frequency of consumption, whether the person who releases the information is trusted, whether it is authoritative, and other factors that will cause this conclusion [2]. Through a preliminary study and two experiments, this research further expands the research of the information processing model in the processing of genetically modified food label information.…”
Section: Theoretical Contributionmentioning
confidence: 73%
See 2 more Smart Citations
“…It may be because consumers have different perceptions of whether tomatoes and corn are GM foods compared to soybeans and rice, which results in insignificant effects. Previous studies have also pointed out the difference in the frequency of consumption, whether the person who releases the information is trusted, whether it is authoritative, and other factors that will cause this conclusion [2]. Through a preliminary study and two experiments, this research further expands the research of the information processing model in the processing of genetically modified food label information.…”
Section: Theoretical Contributionmentioning
confidence: 73%
“…The global commercialization of genetically modified organisms (GMOs) has advancing worldwide at an unprecedented speed [1]. Consumers' attitudes and behavior patterns towards genetically modified organisms will significantly impact the future of the economy [2]. According to the FAO GM Foods Platform, 191.7 million hectares of biotech crops are grown in 70 countries, and about 60% to 70% of the food on the market contains genetically modified ingredients [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is ample evidence that GMOs improve yield and reliability of the food supply [78,79], their diffusion across the world has been shown to depend on a number of factors, including individual personality traits [80], public trust [81], public perception of specific risks and benefits [82], and national regulatory frameworks [83]. Over time, the information provided through media coverage [84] and scientific publications [85] appear to contribute to growing knowledge [86], trust [87], and better health expectations [88], contributing to increased acceptance.…”
Section: Genetically Modified Organisms (Gmos)mentioning
confidence: 99%
“…Additional work found that trust in science and technology is associated with increased trust in specific technologies, such as genetically modified organisms (GMOs), biotechnology, nuclear power, and wind power (Roberts et al, 2013). Work by Hunt and Wald (2020), exploring scientific source credibility-based on measures of scientist's understanding, integrity, agreement, concern, trust, and goodwill (lack of political bias; not career motivated)-found that that the public's views of scientific credibility influenced their views on genetically modified food. Finally, when the public views scientists as knowledgeable, reflective of scientific consensus, and as serving the national interests they are more likely to support scientists making decisions over elected officials, with the most important predictor being that scientists served the national interest (O'Brien, 2013).…”
Section: Technocracy Energy and Climate Changementioning
confidence: 99%